When words matter: A cross-cultural perspective on lyrics and their relationship to musical emotions. (March 2022) - Barradas, Gonçalo T; Sakka, Laura S
Several studies have investigated emotional reactions to instrumental music. However, studies on the effect of lyrics on emotions are limited. Previous studies suggest that the importance of lyrics may vary cross-culturally. The aim of this study was twofold: to investigate the effects of lyrics on aroused emotions and psychological mechanisms with music and to explore whether these differ cross-culturally. Fifty participants from Portugal and Sweden listened to six musical stimuli based on two songs, one representing each culture. These were presented in three versions each: the original, an instrumental, and the instrumental version with lyrics on the screen. The Portuguese and Swedish participants differed notably: the presence of lyrics did not affect listeners' happiness in neither group as predicted, but did increase sadness, albeit only in the Portuguese group. Lyrics also increased nostalgia for the Portuguese listeners as predicted and surprise-astonishment for the Swedish listeners. Regarding the mechanisms, lyrics increased the activation of episodic memory in both groups, and the activation of evaluative conditioning, contagion, and visual imagery in the Portuguese group. The present study indicates that lyrics have an effect on musical emotions and mechanisms which vary between groups of different cultural backgrounds.